Epidemiological Mapping of Dog Bite Cases Reporting To Anti-Rabies Vaccination Out-Patient Unit of A Tertiary Care Hospital - US Saurabha; Ravindra S Kembhavi (Medsci Publications, 2020)
Context: Rabies remains a public health challenge in many parts of the world with over 90% of human rabies cases worldwide attributed to dog bites. In India the annual incidence of dog bite is 1.9%. The study was conducted to analyse the distribution of dog bite cases as per time, place and person. Methodology: A cross-sectional study was conducted between Jan-2016 and Dec- 2017. A total of 228 victims of dog bite were interviewed. They were selected using systematic random sampling technique. Data was analysed using SPSS. Spot maps were prepared. Results: The proportion of adults being bitten by dog was more than that of children. Most of the bites occurred after evening hours. There was similarity in the place of residence and place of occurrence of bite in 81% of the cases. A statistically significant association was seen between the type of occupation and place of occurrence of dog bite. Conclusion: Epidemiological mapping of dog bite cases gives more insight to understand the problem and aids in planning control measures against occurrence dog bite. Most dog bites occurred at hours when the man dog interaction was highest. The individuals working in outdoor type of occupation are at high risk for dog bite.